Continental-scale Atmospheric Impacts of the 2020 Western U.S. Wildfires. (1st February 2023) - Albores, I.S.; Buchholz, R.R.; Ortega, I.; Emmons, L.K.; Hannigan, J.W.; Lacey, F.; Pfister, G.; Tang, W.; Worden, H.M.
Abstract: The wildfire season in the Western United States (U.S.) was anomalously large in 2020, with a majority of burned area due to lightning ignitions resulting in overall fire emissions of carbon monoxide (CO) in the Western region almost 3 times the 2001–2019 average. We used the Community Atmosphere Model version 6 with Chemistry (CAM-chem) to investigate how the 2020 fires in the Western U.S. affected air quality locally as well as in surrounding regions that received transported pollution. Simulations with and without fire emissions over the Western U.S. (32.5–49°N, 115–125°W) in July–December 2020 were used to determine average changes in atmospheric composition across the country. Comparisons against satellite and ground-based column CO observations show that the model generally underestimated CO from fires but adequately reproduced spatial and temporal variability. Simulations showed the 2020 fire season contributed 14.5% to atmospheric CO over the Contiguous United States in September, and ∼ 3% to CO averaged across the Northern Hemisphere; these enhancements lasted several months. Fire emissions in 2020 continued later into the year than usual, resulting in sustained air pollution over the Western U.S. region, with noticeable meridional transport of ozone (O 3 ) and fine particulate matter (PM2.5 ). Finally, we use the model to identify two transported fire pollution events at Boulder, Colorado. Highlights: The 2020 Western U.S. wildfires produced CO emissions 3 times the 2001–2019 average. The fires contributed 0.5 – 14.5% to modeled CO averaged over the United States. Enhancements in surface O 3 and PM2.5 across the U.S. lasted through the fire season.